P110: Are there differences in student academic and clinical performance after rotations at tertiary or community care Emergency Medicine teaching sites?. (May 2019) - Rotenberg, C.; Field, S.
Abstract : Introduction : Canadian undergraduate medical Emergency Medicine (EM) rotations are often completed at either tertiary care centres or regional community hospitals. While the latter offer students exposure to different practice settings and population needs, many students perceive that teaching at tertiary care EM departments is superior to that in community hospitals. At our institution, third year undergraduate medical students complete three-week EM rotation at either a tertiary centre or a community hospital. We compared academic and clinical performance between students trained in tertiary care centres and students trained in community hospitals.Methods : Academic and clinical performance in EM was evaluated based on the results of an EM-specific multiple choice examination (MCQE) and an annual Objective Structured Clinical Exam (OSCE) assessing competency in a broad range of clinical scenarios commonly addressed in EM. The 40-question MCQE is administered quarterly and a mix of old and new questions are used to ensure consistency. The OSCE is administered annually and relies on the same principal to remain consistent. OSCE scores are binary: pass or fail. We reviewed MCQE and OSCE scores from three consecutive cohorts of students. Students were pooled into two groups, tertiary and community, based on the site of their EM rotation. Mean MCQE and OSCE performance were compared between the two groups of students using two-tailed unpaired T tests. Chi squared tests were used to identify significant differences in scores between cohorts.Results : MCQE and OSCE scores from 312 students over three consecutive cohorts were analyzed. Cohorts included 104, 100, and 108 students with 61% trained in tertiary centres (N = 191). Students trained in tertiary centres had a mean MCQE score of 77%. Students from community centres had a mean score of 78%. There was no significant difference in MCQE scores between tertiary- and community-trained students (p = 0.6099). The OSCE pass rate was 97% for students trained in tertiary centres and 98% for students trained in community centres. OSCE pass rates were not significantly different between the two groups (p = 0.8145).Conclusion : Despite student perceptions that training in tertiary care EM centres was superior, objective analysis showed that academic and clinical performance were similar regardless of training site.